A gas emitted by Neurospora crassa - Y. Peleg; R. Aramayo; A. B. Bleeker; R L METZENBERG (Fungal Genetics Reports, 1996)
We investigated whether gases other than carbon dioxide are produced by N. crassa. A peak corresponding to ethylene has been detected using gas chromatography. Mass spectroscopy, however, indicated that the gas produced might be carbon monoxide which, surprisingly, migrated with the same chromatographic retention time as ethylene. Our results emphasize the need for caution when interpreting results based solely on gas chromatographic data.